Women unite [videorecording] : inspiring women in Malaysia to unite for an AIDS-free generation (Malaysia : UNICEF, 2008)
UNICEF calls for everyone to unite to reduce the vulnerability of women and children to HIV
Narrated by Asha Gill
dvd format
Keywords: HIV Infections -- Malaysia; HIV infections -- Malaysia -- Prevention; HIV-positive children